ANALYSIS OF ENTREPRENEURSHIP GUIDANCE FOR THE DISABLED (CASE STUDY AT GRIYA HARAPAN DISABILITY SOCIAL SERVICE CENTER) - Ateng Kusnandar Adisaputra; Suhendi; Iwan Setiawan; Ade Ponirah; Dimas Hardiansyah; Rahayu Kusuma Dewi; Nurhaeti (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2026)
This study aims to analyze the implementation of entrepreneurial guidance for people with disabilities at the Regional Technical Implementation Unit of the Griya Harapan Difabel Social Service Center of the West Java Provincial Social Service. The research background is the persistently low levels of work participation and economic independence among persons with disabilities, despite various national regulations that guarantee their right to employment and entrepreneurship. The research employs a descriptive qualitative approach, collecting data through Field Research, Observation, Interviews, and Research. The study's results indicate that local government policies provide a solid foundation for the development of entrepreneurship among people with disabilities; however, their implementation still requires stronger coordination and sustainability. The guidance program at the Regional Technical Implementation Unit runs through vocational skills training, entrepreneurship guidance, direct practice, and business mentoring. This program has been shown to enhance participants' skills, confidence, and ability to start or develop an independent business.